The spurious texts of Philo of Alexandria : a study of textual transmission and corruption with indexes to the major collections of Greek fragments - Royse, James Ronald. (Arbeiten zur Literatur und Geschichte des hellenistischen Judentums, 1991)
The transmission of Philo of Alexandria's works is very complex, and genuine works are preserved in the original Greek, and in ancient Armenian and Latin translations. There are also many excerpts attributed to him in medieval catenae and florilegia, and in quotations in Church writers. The task undertaken here is to discriminate as far as possible between the genuine and the spurious within the textual history of Philo. An analysis of the sources of the fragments of Philo is followed by a listing of sixty-one texts which are demonstrably spurious, deriving (as is shown here) from various sources, including the Bible, Church writers, classical authors, and Josephus. Also included is a survey of the complete books which have been mistakenly assigned to Philo. An Index locorum provides identifications of the Philonic texts found in all the principal collections of fragments. Many of the identifications of spurious and of genuine fragments are made here for the first time.